Demographic and Clinic Characteristics and Risk Factors of Molluscum Contagiosum in Children - Takci, Zennure; Karatas, Arzu; Bas, Yalcin; Tekin, Ozlem; Kalkan, Goknur; Seckin, Havva Yildiz; Akbayrak, Atiye; Sezgin, Sercan; Demir, Osman; Takci, Sahin (Journal of the Pakistan Medical Association, 2022)
Objective: To address the gap in evidence related to molluscum contagiosum in children by focusing on demographic and clinical features as well as risk factors. Method: The multicentre, prospective, clinical study was conducted at four hospitals in Ankara and Tokat cities of Turkey from August 1, 2014, to August 5, 2019, and comprised patients aged 18 years diagnosed with molluscum contagiosum. Data about demographics, day nursery and preschool attendance, the seasons when the disease occurred, any use of Turkish baths and swimming pools, history of personal/familial atopy, coexistence of diseases, disease duration, courses, number of lesions and anatomic localisation. Data was analysed using SPSS 19. Results: Of the 286 patients, 130(45.5%) were girls and 156(54.5%) were boys. The overall mean age was 5.94±3.95 years. The median duration of the disease was 5 weeks (interquartile range: 3.00-12.00 weeks). There was a significant number of cases with family history 18(48.6%) in the 0-3 age group (p=0.027). History of personal atopy was significantly high in the winter season (p<0.05). Patients with >20 lesions had used swimming pools significantly more frequently than the rest (p=0.042). The trunk was the most commonly involved region 162(56.6%). Conclusion: Providing prospective data about demographics, clinical characteristics and risk factors of molluscum contagiosum in children will lead to appropriate preventive and therapeutic measures. Key Words: Children, Molluscum contagiosum, Epidemiology.